Agricultural Inputs for Organic Agriculture - K. Soytong; J. J. Song; R. Tongon (My University, 2021)
Sustainable development concerns on saving energy and the environmental friendly reservation and to serve healthy and safety food.The history of agricultural production using chemical fertilizers, pesticides and other synthetic chemicals for crop and animal production is to increase yield become harzardous to human being and living things in our environments.We have proposed the modern organic agriculture model to serve the sustainable development goal (SDGs) that possible be a new combination practical technology for organic agriculture.The research investigation is still needed to find more bioproducts and natural producrts to contribute knowledge for non-agrochemical production (NAP) transition period to organic agricultural production.The demonstration organic model is proposed which consisted of organic crop production, organic animal production, understanding bioproducts and natural products as agricultural inputs, seed production, food preservation, animal feed, organically certification by trusted agencies, organic markets and practical training.The certified agricultural inputs for organic agriculture is needed for acceptable used eg.biological fertilizers (compost) and biofungicides, bioinsecticides, bioherbicides, and biological nutrition.The other combination techniques are proposed as cultural practice, crop rotation, inter-cropping, organic amendment, biochar technology.The net house, greenhouse in closed or semi-closed system to control temperature and relative humidity are also concerned.The herbs or medicinal plants, and natural wood vineagar to eliminate plant pathogens and insects are introduced.The light and yellow traps, natural pheromones, natural sulfur, white oil, repellent plants, neem-oil etc. are recommended.We have been conducted to investigate the bioproducts sine 1989 and those bioproducts are gradually contributed to farmers.Our research successfully findings are contributed as bio-remediation and bio-decomposer for revitalizing the soil to get rid of the heavy metals residue in the cultivated soil and make compost, the different formulations of organic-inorganic biological fertilizers with high nitrogen, phosphorous, potassium, calcium and magnesium etc. and biological nutrients for plant growth to be used instead of chemical fertilizers.Chaetomium myco-fungicide for broad spectrum plant disease control and the biodegradation natural product fine particles acts as natural elicitor for plant immunity.We have promoted to do organic agricultural production and certification until delivery to the markets.
Keywords: Agronomic Practices and Intercropping Systems